S86 A single-blind, multicentre, multinational, randomised controlled trial of online singing for Lung Health (SLH) vs usual care for people with COPD: the Singing for Health, Improving Experiences of Lung Disease (SHIELD) Trial. (11th November 2022) - Philip, KEJ; Buttery, SC; Bowen, S; Lewis, A; Alghamdi, SM; Williams, PJ; Alasmari, AM; Alsulayyim, AS; Orton, CM; Conway, F; Chan, L; Vijayakumar, B; et al.
Abstract : Background: Singing for Lung Health (SLH) is an arts-based non-pharmacological intervention for people with long-term respiratory conditions that aims to improve symptoms and quality of life (QOL). Current research suggests face-to-face SLH can improve aspects of QOL and physical performance. There is interest in online, remotely delivered SLH, however no previous studies have assessed its impact. Methods: A single blind randomised controlled trial comparing the impact of 12 weeks of once-weekly online SLH to usual care (UC) on health related quality of life (HRQoL) (RAND SF-36 Mental (MHC) and Physical (PHC) health composite scores). Secondary outcome measures were breathlessness (MRC dyspnoea scale and Dyspnoea-12), physical activity (daily step-count and PROactive cPACC), balance confidence (ABC score), anxiety (GAD-7), depression (PHQ-19) and COPD symptoms (CAT score). Results: 115 participants with stable COPD were recruited and allocated into well-matched study arms. Median (IQR) age of 69 (62–74); 56.5% female; 87.8% White British ethnicity; 80% previously participated in pulmonary rehabilitation; MRC dyspnoea scale median (IQR) 4 (3–4); FEV1% predicted 49 (35 to 63); 13.0% current smokers, mean (SD) packyears 33.5 (20.3), BMI 25.7 (6.3); 10.4% were using supplementary oxygen therapy. 50 participants in each arm completed the study. Compared with UC, SLH participation was associated with preferable changes to the RAND SF-36 PHC (regression coefficient 1.77 [95%CI 0.11 - 3.44]; p=0.037)) but not MHC. No statistically significant between groups differences were observed in secondary outcome measures in the prespecified intention to treat analyses. In a prespecified responder analysis based on achieving a 10% improvement from baseline, the response rate for PHC was 32% of the SLH arm and 12.7% of UC (p=0.024). A statistically significant between group difference was not found in relation to a 10% improvement from baseline for the SF-36 MHC. More adverse events were reported in the UC(n=22) than SLH(n=16) arm. Discussion & Conclusion: Our findings suggest that a 12-week online SLH intervention can improve the physical component of HRQoL for people with COPD. Online SLH may be a useful addition to COPD management for selected individuals. Trial Registration: ClinicalTrials.gov NCT04034212